Long-term serial non-invasive multislice computed tomography angiography with functional evaluation after coronary implantation of a bioresorbable everolimus-eluting scaffold: the ABSORB cohort B MSCT substudy. (16th March 2017) - Onuma, Yoshinobu; Collet, Carlos; van Geuns, Robert-Jan; de Bruyne, Bernard; Christiansen, Evald; Koolen, Jacques; Smits, Pieter; Chevalier, Bernard; McClean, Dougal; Dudek, Dariusz; Windecker, Stephan; Meredith, Ian; et al.
Abstract: Aims: Multimodality invasive imaging of the first-in-man cohort demonstrated at 5 years stable lumen dimensions and a low rate of major adverse cardiac events (MACE). However, the long-term non-invasive assessment of this device remains to be documented. The objective was to describe the 72-month multislice computed tomography (MSCT) angiographic and functional findings after the implantation of the second iteration of the fully resorbable everolimus-eluting polymeric scaffold. Methods and results: In the ABSORB Cohort B trial patients with non-complex de novo lesions were treated with second iteration bioresobable vascular scaffold (BVS). MSCT angiography was performed as an optional investigation at 18 months; patients were reconsented for a second investigation at 72 months. MSCT data were analysed at independent core laboratories for quantitative analysis of lumen dimensions and for calculation of fractional flow reserve derived from computed tomography (FFRCT ). From the overall Cohort B (101 patients), 53 patients underwent MSCT imaging at 72 months. The MACE rate was 1.9% (1/53). At 72 months, the median minimal lumen area (MLA) was 4.05 mm 2 (interquartile range [IQR]: 3.15–4.90) and the mean percentage area stenosis was 18% (IQR: 4.75–31.25), one scaffold was totally occluded. In 39 patients with paired MSCT analysis, the MLA significantly increased from the first to the second follow-up (Δ = 0.80 mm 2, P  = 0.002). The change in the median FFRCT scaffold gradient between time points was zero. Conclusion: The long-term serial non-invasive MSCT evaluation with FFRCT assessment after bioresorbable scaffold implantation confirmed in-scaffold late lumen enlargement with the persistence of normalization of the FFRCT . Clinical trial registration: URL: http://www.clinicaltrials.gov . Unique identifier: NCT00856856.